Medical experimentation and the roots of COVID-19 vaccine hesitancy among Indigenous Peoples in Canada - Mosby, Ian; Swidrovich, Jaris (Canadian Medical Association journal (CMAJ), 2021)
For a start, doctors and other health professionals in Canada need to educate themselves before going into communities to administer COVID-19 vaccines. Too many are unaware of Canada's shameful histories of racially segregated health care and medical experimentation, and therefore misunderstand the nature of vaccine hesitancy. Public health messaging about the risks of SARS-CoV-2 infection and the benefits of receiving the vaccine also must clearly be positioned in a way that speaks to Indigenous Peoples' historical and contemporary experiences with Canadian settler colonialism. Risk attributes must also be described individually rather than simply categorizing Indigeneity as an individual risk category. This means jettisoning a one-size-fits-all public health messaging strategy. Pandemic messaging will be more effective if delivered directly by Indigenous Elders, leaders and health practitioners who have trust and credibility in their communities. For many communities, this means that public health messaging needs to focus not only on the health and wellness of the people receiving the vaccine, but also on the health and wellness of families, communities, the land and the next seven generations.